Nursing Care for Patients with Vulnus Laceratum in the Emergency Unit: A Case Report - Cahyaninggalih, Aldila (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Vulnus Laceratum is a disruption of the continuity of tissue so that there is a separation of tissue that was initially normal; torn wounds occur due to severe violence that severs the tissue. Vulnus Laceratum is the third most common type of injury in Indonesia, with a percentage of 23.2%. Nursing problems that often arise in patients with vulnus laceratum are acute pain, impaired skin and tissue integrity, and risk of infection. The knowledge and role of nurses are essential in the rapid treatment of vulnus laceratum patients at risk of bleeding, infection and even disability. This case study aims to analyze the application of nursing care to patients with vulnus laceratum. Nursing care methods using the SDKI, SLKI, and SIKI approaches. The results of the assessment obtained four male patients, the cause of vulnus laceratum 2 cases due to vehicle accidents, 1 case due to blunt objects, and 1 case due to sharp objects. The nursing diagnoses that appear are impaired skin and tissue integrity, acute pain, risk of ineffective cerebral perfusion, and risk of infection. Nursing interventions include wound care, wound suturing, pain management, vital sign monitoring, and infection prevention. During the implementation process, all interventions were carried out. Evaluation of nursing care with impaired skin and tissue integrity disorders resolved on the 10th and 30th days, acute pain resolved on the third day, risk of infection on the seventh day, and risk of ineffective cerebral perfusion 1 hour after implementation. The results of this case study are expected to increase knowledge and complement existing sources so that knowledge and management of vulnus laceratum are appropriate and fast.